Meta-analysis examining the association between low platelet monoamine oxidase levels and Zuckerman's sensation seeking scale in a sex dependent manner - Winfield, Jordan; Mendez, Ian A.; Frietze, Gabriel A. (Frontiers in Psychology, 2025)
Monoamine oxidase (MAO) is an enzyme in the brain responsible for breaking down neurotransmitters. MAO levels can be measured in humans by collecting blood platelets. Low platelet MAO levels in healthy individuals are associated with personality differences, such as increases in sensation seeking. In this meta-analysis, we investigated the association between low platelet MAO activity and sensation seeking behavior, as measured by Zuckerman's Sensation Seeking Scale (SSS). To identify studies to include in this meta-analysis, a preliminary database was produced by searching PsycInfo, Medline, PubMed, ProQuest, and ScienceDirect, from the time period of January 01, 1970 through August 01, 2022. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed for study inclusion. Fourteen studies with a total of 24 correlations and 1,470 participants were included in the analyses. Across 24 independent effect sizes, the correlations ranged from −0.74 to 0.40. The Random Effects Model (REM) yielded a weighted average correlation of −0.22 (95% CI = −0.31, −0.13), indicating an inverse relationship where lower levels of MAO tend to be associated with higher levels of SSS. A subgroup analysis was used to examine the effects of gender. The REM yielded a weighted average correlation of −0.22 (95% CI = −0.33, −0.10) for the effect sizes of males, −0.22 (95% CI = −0.47, 0.06) for the effect sizes of females, and −0.23 (95% CI = −0.38, −0.06) for the effect sizes that included both males and females. The subgroup analysis did not reveal differences between males and females on the association between human blood platelet MAO levels and SSS. Our hypothesis that there is a negative association between MAO levels and SSS was supported. These findings have potential clinical implications suggesting that MAO platelet concentrations could be used as a potential biomarker for identifying maladaptive behaviors.